Risky tax shields and risky debt: An exploratory study (2010)
This article (1) identifies three sources of risk for tax shields (TS): Two of them are associated with debt risk and one is associated with operating risk. (2) A set of conditions for defining risky debt associated with cash flow, not with earnings, is presented. (3) It further shows that realization of TS for finite cash flows in a period of time t is correlated with Earnings before Interest and Taxes (EBIT) plus Other Income (EBITO), not with interest expenses at time t. With the results of a Montecarlo Simulation the behavior of TS, Cash Flow to Debt and EBITO are examined. In conclusion, the article suggests that it is not reasonable to define the risk of TS as measured by a single discount rate, but rather as a mix of debt risk and operating risk.